2018
DOI: 10.1007/s10067-018-3989-2
|View full text |Cite|
|
Sign up to set email alerts
|

Drug survival and effectiveness of ustekinumab in patients with psoriatic arthritis. Real-life data from the biologic Apulian registry (BIOPURE)

Abstract: This study aims to evaluate the drug survival and effectiveness of ustekinumab in psoriatic arthritis (PsA) patients naïve to biologics or inadequate responders to tumor necrosis factor (TNF-IR) inhibitors in real life. PsA patients starting ustekinumab were enrolled from 2014 to 2016. Joint involvement, peripheral or axial, Psoriatic Area Severity Index, Disease Activity Psoriatic Arthritis (DAPSA), Lee Enthesitis Index, Health Assessment Questionnaire, body mass index, comorbidities, co-therapies, mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
3
21
0
1
Order By: Relevance
“…Confounding by indication was possible; disease severity was generally mild in all cohorts and was within the same range across existing and initiated therapy, but some differences were seen for prior csDMARD use. Previous registry studies provided similar results but were conducted either outside the United States [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] or they used a subset of PsA patients from a registry in the United States that was designed primarily for patients with rheumatoid arthritis [40][41][42][43]. Our study used data from a registry in the United States that was specifically designed to collect information about patients with PsA.…”
Section: Discussionmentioning
confidence: 95%
“…Confounding by indication was possible; disease severity was generally mild in all cohorts and was within the same range across existing and initiated therapy, but some differences were seen for prior csDMARD use. Previous registry studies provided similar results but were conducted either outside the United States [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] or they used a subset of PsA patients from a registry in the United States that was designed primarily for patients with rheumatoid arthritis [40][41][42][43]. Our study used data from a registry in the United States that was specifically designed to collect information about patients with PsA.…”
Section: Discussionmentioning
confidence: 95%
“…In this context several studies have found elevated serum IL-23 levels in patients with SpA, PsO and PsA [37][38][39][40][41][42]. Therefore, close control of inflammation by anti-IL-23 drugs may turn off the disease activity and consequently the structural damage [5,9,10,43].…”
Section: Discussionmentioning
confidence: 99%
“…In general, ACR and PASI responses were achieved irrespective of MTX use among the overall study populations in both trials, though the response rates were somewhat numerically higher among patients who did not receive concomitant MTX than among those undergoing combination therapy of ustekinumab plus MTX 4–6. A recent analysis of real-world data from a patient registry (BIOPURE) provided findings similar to those from the PSUMMIT trials; biologic-naïve patients tended to have longer treatment persistence and better clinical outcomes than those who previously had an inadequate response to one or more anti-TNF therapies 11. In addition, there was no apparent effect of concomitant MTX use on ustekinumab treatment persistence in this registry.…”
Section: Discussionmentioning
confidence: 79%